Evaluation of 11 microsatellite loci for their use in paternity testing in Yugoslav Pied cattle (YU Simmental cattle) - J. Stevanovic; Z. Stanimirovic; V. Dimitrijevic; M. Maletic (Czech Journal of Animal Science, 2010)
Eleven microsatellite loci (TGLA227, BM2113, TGLA53, ETH10, SPS115, TGLA126, TGLA122, INRA023, ETH3, ETH225, BM1824) were evaluated for their use in paternity testing in the Yugoslav Pied cattle (YU Simmental cattle) population in Serbia. A total of 40 animals were tested. At the 11 tested loci, a total of 91 alleles were detected. The mean number of alleles per locus was 8.273. Polymorphism information content (PIC) values ranged from 0.58 to 0.88 with the mean value of 0.72. The most informative loci were: TGLA53 (14 alleles, PIC = 0.88), TGLA227 (11 alleles, PIC = 0.82), INRA023 (11 alleles, PIC = 0.86), BM2113 (9 alleles, PIC = 0.80). Combined power of discrimination (CPD) for the 11 microsatellite loci was 0.999. The results of the present study confirm that the analysed set of 11 microsatellite markers recommended by ISAG is suitable for paternity testing in Yugoslav Pied cattle in Serbia.